Unraveling conflict amongst Muslim female characters in Malay chick lit - Abu Ujum, Diana; Mohd Jan, Jariah (Taylor and Francis Group, 2022)
Muslim and Malay women writers from Malaysia who publish contemporary romances, better known as Malay chick lit (sharing similar lucrativeness to Western chick lit), would be hard-pressed to call their work significantly dramatic or expressing a specific brand of literariness to be included in highbrow Malay literature. Nonetheless, best-selling Malay romance novels of the 21st century, or Malay chick lit, offer a rich platform of female protagonists and character tropes that deal with a certain dailiness in many points recognizable in the real world (i.e. setting, technology and whatever may be perceived as possessing Malay characteristics such as speech and behavior tied to cultural nuances). Such character types and tropes consis- tently reflect aspects of negotiation and conflict throughout structured plots that are considered typical in Malay or even Malaysian romance.